STRATEGI INTEGRASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM KEGIATAN EKSTRAKULIKULER PRAMUKA UNTUK MEMBENTUK KARAKTER RELIGIUS SISWA DI MAN 8 JOMBANG - Imam Wahyudi; Jumari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the strategy of integrating Islamic Religious Education (IRE/PAI) values into Scout extracurricular activities as a systematic effort to cultivate religious character in students at MAN 8 Jombang. The study is grounded in a tangible gap between students' theoretical comprehension of Islamic norms and their ability to actualize those norms in daily behavior. It aims to: (1) describe the integration models applied within Scout activities; (2) analyze the impact of such integration on students' religious character formation; and (3) identify the supporting and inhibiting factors in its implementation. A qualitative case study approach was employed, with data collected through in-depth interviews, participatory observation, and documentation, involving PAI teachers across four subject areas (Qur'an-Hadith, Islamic Creed and Ethics, Fiqh, and Islamic Cultural History), Scout leaders, and students. Data analysis followed the Miles and Huberman model, validated through source and technique triangulation. Findings reveal that PAI-Scout integration at MAN 8 Jombang operates through three Fogarty models: connected (linking classroom content with field activities), nested (embedding multiple affective-cognitive targets within a single activity), and shared (using joint activities as integration vehicles). The most significant impact is observed in the strengthening of moral action within Lickona's character framework, particularly in the domains of worship discipline, honesty, responsibility, and social care. Key supporting factors include institutional policy support and personal teacher-leader collaboration, while primary obstacles are unstructured institutional coordination and disparities in students' motivation.